Selective neck dissection for treating node-positive necks in cases of squamous cell carcinoma of the upper aerodigestive tract - Antonio, Jamile Karina (2008)
CONTEXT AND OBJECTIVE: Modifi ed radical neck dissection (MRND) is the classical treatment for neck metastases of squamous cell carcinoma (SCC) of the upper aerodigestive tract. However, it may still be accompanied by signifi cant sequelae. One alternative for this treatment would be selective neck dissection (SND), which has a lower incidence of sequelae. The aim of this study was to defi ne which neck metastasis cases would really be suitable candidates for SND. DESIGN AND SETTING: Retrospective clinicalsurgical trial at the Division of Head and Neck Surgery, Faculdade de Ciências Médicas da Santa Casa de São Paulo (FCMSCSP). METHODS: We retrospectively studied 67 patients with SCC of the upper aerodigestive tract, divided into two groups: 1) 47 patients treated by means of SND (node-negative or node-positive), 2) 20 patients treated by means of MRND (all node-positive). RESULTS: Our results demonstrated that there was no difference between the patients treated with SND or MRND in relation to disease evolution, and that the main prognostic factor was lymph node involvement. We observed that patients with pharyngeal SCC and older patients presented worse evolution and would probably not be suitable candidates for SND. CONCLUSIONS: SND may be a good option for treating node-positive necks in selected cases.